A small segment of the MAT alpha 1 transcript promotes mRNA decay in Saccharomyces cerevisiae: a stimulatory role for rare codons. - Caponigro, G (1993)
Differences in decay rates of eukaryotic transcripts can be determined by discrete sequence elements within mRNAs. Through the analysis of chimeric transcripts and internal deletions, we have identified a 65-nucleotide segment of the MAT alpha 1 mRNA coding region, termed the MAT alpha 1 instability element, that is sufficient to confer instability to a stable PGK1 reporter transcript and that accelerates turnover of the unstable MAT alpha 1 mRNA. This 65-nucleotide element is composed of two parts, one located within the 5' 33 nucleotides and the second located in the 3' 32 nucleotides. The first part, which can be functionally replaced by sequences containing rare codons, is unable to promote rapid decay by itself but can enhance the action of the 3' 32 nucleotides (positions 234 to 266 in the MAT alpha 1 mRNA) in accelerating turnover. A second portion of the MAT alpha 1 mRNA (nucleotides 265 to 290) is also sufficient to destabilize the PGK1 reporter transcript when positioned 3' of rare codons, suggesting that the 3' half of the MAT alpha 1 instability element is functionally reiterated within the MAT alpha 1 mRNA. The observation that rare codons are part of the 65-nucleotide MAT alpha 1 instability element suggests possible mechanisms through which translation and mRNA decay may be linked.